2017
DOI: 10.1080/01446193.2017.1296171
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and institutional logics in construction safety management: the case of climatic heat stress

Abstract: We employed a Glaserian grounded theory approach to explore the gap between behavioural safety and its unsatisfactory outcomes. Data were collected through ethnographic studies on the practice of managing heat stress on thirty-six construction sites in Hong Kong and Chonqing in mainland China. Two core concepts, institutions and institutional logics, are generated and defined to explain why safety rules do not necessarily produce safety behaviours. At society level, we explicated two pairs of institutional log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
(43 reference statements)
1
30
0
1
Order By: Relevance
“…privileged or standalone knowledge); it is rather a doing, an integrated attribute of everybody's practice on site. However, this perspective does not adequately address the professionalized safety-specific practice, in which safety in some senses is something in itself (Jia et al 2017). Therefore, in order to be able to distinguish between the differences of opinion, with regard to how safety is achieved, we also draw on an understanding of safety as positioned and essentially powered (Antonsen 2009, Hale andBorys 2013a).…”
Section: Methodology: the Practice Of Safety As Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…privileged or standalone knowledge); it is rather a doing, an integrated attribute of everybody's practice on site. However, this perspective does not adequately address the professionalized safety-specific practice, in which safety in some senses is something in itself (Jia et al 2017). Therefore, in order to be able to distinguish between the differences of opinion, with regard to how safety is achieved, we also draw on an understanding of safety as positioned and essentially powered (Antonsen 2009, Hale andBorys 2013a).…”
Section: Methodology: the Practice Of Safety As Surveillancementioning
confidence: 99%
“…Safety culture, however, has also been criticized for essentially being a management tool aimed at diffusing management values under the guise of the "right" safety culture (Antonsen 2009). These discourses cover many aspects of safety management, but they have also been shown to work against the intentions of creating safer construction sites and lowering incident rates (Jia et al 2017, Provan et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To Conclude: Alternative Thinking and a Call for Research I finish with a useful glimpse of how a utopian future for safety and production might be realised. Jia et al (2017) considered this concept whereby two institutional logics were identified, at a project organisation level, through ethnographic observation: a protection logic and a production logic. In the former, workers "intrinsically protect their personal interest by staying safe as much as they can" and in turn, if employers demonstrate their positive attitude to safety then they concluded that workers are more likely to be motivated and increase productivity.…”
Section: Productivity and Its Measurement Conundrummentioning
confidence: 99%
“…industrialized building processes. Both these studies, and the work by Jia et al (2017) and Gluch and Svensson (2017), show the importance of studying multiple levels in order to grasp the full complexity of managerial processes in construction. The concept of sensemaking has been picked up several times in recent CMR contributions, for example by Fellows and Liu (2016) in relation to cultural differences in project environments and by Kreiner (2006) and Volker (2012) in the context of architect selection processes.…”
Section: ) Onmentioning
confidence: 99%